The Drosophila SET domain encoding gene dEset is essential for proper development. - Stabell, M.; Bjørkmo, M.; Aalen, R.B.; Lambertsson, A. (Hereditas, 2006)
We have identified dEset, the fly homolog of human SETDB1 and mouse ESET histone lysine methyltransferases (HKMTases) that methylates the lysine 9 residue of histone 3 (H3-K9) and negatively regulates transcription of target genes. By using spatio-temporal RNA interference we show that dEset is required at several stages of development coinciding with ecdysone pulses, possibly as a repressor of transcription of target genes. Several interacting partners, for example USP, spire, and cut up were identified in a yeast two-hybrid screen. The spatio-temporal expression profiles of dEset and its potential partners suggest that they may act together or even in a larger complex.